The Incidence of Persistent Symptom and Echocardiographic Findings in Survivors of COVID-19 Infection with Mild Symptoms - Almazini, Prima; Kuncoro, Ario S; Ariani, Rina; Rudiktyo, Estu; Sukmawan, Renan; Soesanto, Amiliana M (Jurnal Kardiologi Indonesia, 2025)
In “The Incidence of Persistent Symptom and Echocardiographic Findings in Survivors of COVID-19 Infection with Mild Symptoms” (Indonesian Journal of Cardiology, 43(1), 9-15. https://doi.org/10.30701/ijc.1160), there is an error noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1160. The error occurs only in the PDF; the DOI listed in the article metadata is already correct.The publisher apologizes for any inconvenience caused by this error.DOI of original article: https://doi.org/10.30701/ijc.1160